Does the use of BariBoard™ improve adequacy of chest compressions in morbid obesity? A pilot study using a simulation model. Issue 6 (November 2022) - Goulding, Kate; Marchetti, Rosa; Perera, Rushan; Johnson, Richard; Bailey, Michael; Secombe, Paul
Abstract: Background: Obesity is a growing health problem worldwide. Morbid obesity has been associated with significant barriers to effective thoracic cage compression during cardiopulmonary resuscitation. Objective: The BariBoard™ purports to improve adequacy of chest compressions in morbidly obese patients. This study uses a simulation model to evaluate this. Methods: This was a prospective blinded randomised-controlled crossover pilot trial using a simulation model of obesity. Participants, recruited from hospital departments and prehospital services, performed 2 minutes of continuous compressions on mannequins modified to emulate a morbidly obese patient. Participants were randomised by coin toss to a sequence of either control/intervention or intervention/control, with the BariBoard™ in the intervention arm. Accelerometers measured chest wall movement during compressions. The primary endpoint was a composite measure of compression adequacy (rate, depth, and recoil). Secondary endpoints comprised the individual components of the composite outcome, as both dichotomous outcomes (adequate vs. inadequate) and continuous variables. All endpoints were adjusted for potential confounders. Results: Of 205 participants recruited, 201 were analysed. There was a significant difference in the primary outcome between the control and intervention arms (13.4% vs. 4.5%, respectively, p = 0.001) and between the control and intervention arms for the secondary endpoints of adequate compression depth (31.3% vs. 15.9%, p < 0.001) and recoil (63.7% vs. 41.3%, p < 0.001). After adjustment for confounders and interactions, there was no difference in overall efficacy (odds ratio: 0.62, 95% confidence interval: 0.20–1.90, p = 0.40). Conclusion: This pilot study describes the successful assessment of a device using a simulation model of obesity. Within these constraints and after adjustment for confounders, use of the BariBoard ™ did not improve efficacy of chest compressions.